ANALYSIS OF ELEMENTARY SCHOOL STUDENTS’ UNDERSTANDING OF ARITHMETIC CONCEPTS THROUGH A ROPE-JUMPING GAME - Anisatul Lathifah; Syauqia Salsabila; Dita Dwi Amelia; Milakul Asyifah; Sulis Janu Hartati (IKIP SARASWATI TABANAN, 2026)
Arithmetic instruction in elementary school is often presented abstractly, making it difficult for students to understand the concepts meaningfully. One alternative contextual learning approach that aligns with the concrete operational stage is the use of local games. This study aims to describe the implementation of the jumping rope game as a medium for arithmetic learning and to measure students' understanding of the arithmetic concepts that arise during the game. This study uses a quantitative, survey-based approach with a sample of 56 grade III students from SDN Keputih 245 Surabaya. Data were collected through structured observation and guided oral tests, then analyzed using descriptive statistics in the form of frequency and percentage. The results showed that the jumping rope game included the concepts of counting and units of length, which were understood by all students (100%). In comparison, the concept of simple counting operations was understood by some students (50%), and the concept of time was still understood by a small number of students (25%). These findings show that jumping rope has the potential to be a context-rich and engaging medium for arithmetic learning, especially in supporting meaningful understanding of concepts among elementary school students.